FRI0474 Does axial spondyloarthritis phenotype correlate with imaging morphotype?. (15th June 2017) - Baraliakos, X; Szumski, A; Jones, HE; Gensler, L
Abstract : Background: Traditionally, radiographic imaging was used to describe morphological differences between various types of axial SpA (axSpA). The advent of MRI has advanced understanding of disease, enabled earlier diagnosis and visualization of structural changes, and facilitated the identification of non-radiographic axial SpA (nr-axSpA). The magnitude of the pathologic changes in the axial skeleton is used to quantify inflammatory and structural outcomes of clinical trials and treatment of patients with axSpA. Objectives: To examine the MRI morphology of sacroiliitis (SI) and vertebral corner lesions in patients with primary (1°, no psoriasis) and secondary (2°, with psoriasis) axSpA. Methods: This posthoc analysis was performed on data from patients with axSpA enrolled in the EMBARK trial (NCT01258738 ). Only patients with baseline MRI lesions were included. Symmetric and asymmetric SI, structural lesions, and corner inflammatory lesions were analyzed in 1° axSpA vs 2° axSpA patients. Data were analyzed using one-way analysis of variance for continuous parameters, chi-square tests, or Fisher's exact tests for categorical parameters. Results: The baseline demographics and disease characteristics between the 122 patients with 1° axSpA and 19 with 2° axSpA were similar. Asymmetric sacroiliitis was seen in significantly fewer 1° (43%) vs 2° (68%) axSpA patients. There were no differences in mean SpondyloArthritis Research Consortium of Canada (SPARCC) scores between 1° and 2° axSpA for any of the 4 SI joint (SIJ) quadrants. However, the lower iliac quadrants had the highest SPARCC SIJ score and the upper iliac quadrants had the lowest SPARCC SIJ scores. When analyzing the 4 spine quadrants (lower/upper anterior and lower/upper posterior), 1° patients had higher total SPARCC spine scores than 2° patients for all 4 quadrants at baseline. Collapsing the 4 quadrants shows that 1° axSpA patients had higher SPARCC MRI of the entire spine (23 discovertebral units [DVU]; mean=5.7) compared with 2° axSpA patients (mean=2.7). Conclusions: We found 1° axSpA patients had more symmetric sacroiliitis and extensive spinal bone marrow edema compared with 2° axSpA patients. In addition, women appeared to have more asymmetric sacroiliitis. These data may help physicians accurately diagnose patients and decide best treatment options. Disclosure of Interest: X. Baraliakos: None declared, A. Szumski Employee of: inVentiv, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, L. Gensler Consultant for: AbbVie, Janssen, Novartis, Pfizer